Identifying Neurotic Disorders In Irritable Bowel Syndrome And Studying The Effectiveness Of Cognitive Psychotherapy In Them - Gafurova, Sabohat Shayunusovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article presents an analysis of the results of measures to identify anxiety-phobic disorders observed in irritable bowel syndrome, improve medical psychological support, and treat disorders in the patient’s psyche using psychotherapy methods. A statement was made about the importance of psychotherapeutic support in irritable bowel syndrome and achieving the intended result in a short time.